Real And Accruals Earnings Management And Value Relevance Of Accounting Information Among Indonesian Listed Companies - Subekti, Imam (2012)
The outbreak of the 1997 East Asian financial crisis, weak corporate governance practices in Indonesia and their impact on the relations between earnings management and value relevance of accounting information have motivated the present study to pursue the following objectives: (1) to examine the tactics employed by Indonesian public listed companies to conduct earnings management in the attempt to avoid reporting losses, (2) to investigate the relationship between accounting information (earnings and book value of equity) and firm value, and (3) to investigate the effect of earnings management practices on the value relevance of accounting information. The sample of this study comprises 97 public companies listed in the Indonesian Stock Exchange over the period of 1995 to 2006 with 1164 firm-years observations. Panel data regression was employed to test the hypotheses. The results show that Indonesian public companies tend to perform real earnings management rather than accruals earnings management to avoid reporting losses. Real activities which are used as vehicle to perform earnings management are cash flow from operation, production costs, and discretionary expenses. On the other hand, accruals accounts are managed through the use long-term accruals. The results also reveal that earnings and book value of equity are still relevant in measuring firm value